DNA methylation in Drosophila melanogaster may depend on lineage heterogeneity - Redchuk, T.A.; Rozhok, A.I.; Zhuk, O.W.; Kozeretska, I.A.; Mousseau T.A. (Цитология и генетика, 2012)
DNA methylation has been discovered in Drosophila only recently. Current evidence indicates that de novo methylation patterns in drosophila are maintained in a different way compared to vertebrates and plants. As the genomic role and determinants of DNA methylation are poorly understood in invertebrates, its link with several factors has been suggested. In this study, we tested for the putative link between DNA methylation patterns in Drosophila melanogaster and radiation or the activity of P transposon. Neither of the links was apparent from the results, however, we obtained some hints on a possible link between DNA methylation pattern and genomic heterogeneity of fly lineages. Метилирование ДНК описано у дрозофилы сравнительно недавно. Современные данные свидетельствуют о том, что механизмы метилирования de novo у дрозофилы отличаются от таковых у позвоночных животных и растений. Поскольку на сегодня роль метилирования у беспозвоночных окончательно не выяснена, этот процесс связывают с несколькими факторами. В настоящем исследовании проверена потенциальная связь между метилированием ДНК у дрозофилы, радиоактивным загрязнением и активностью Р транспозона. Наличие такой связи не подтверждено полученными результатами. В то же время получены свидетельства возможной связи метилирования ДНК с гетерогенностью популяций. Метилування ДНК було описано у дрозофіли досить недавно. Сучасні дані свідчать про те, що механізми метилування de novo у дрозофіли відрізняються від таких у хребетних тварин та рослин. Оскільки зараз роль метилування у безхребетних остаточно не з’ясована, цей процес пов’язують з кількома факторами. В даному дослідженні перевірено потенційний зв’язок між метилуванням ДНК у дрозофіли, радіоактивним забрудненням та активністю Р транспозона. Наявність такого зв’язку не підтверджено одержаними результатами. Натомість отримано дані, що свідчать про можливий зв’язок метилування ДНК з гетерогенністю популяцій.